(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article provides an in-depth analysis of exact differential equations and the integrating factor method. It explores the theoretical foundations, practical applications, and recent advancements in this field of mathematics. The study emphasizes the importance of these concepts in solving various mathematical and real-world problems, particularly in physics and engineering